2022
DOI: 10.1001/jamacardio.2021.5244
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Clopidogrel Monotherapy After 1 to 2 Months of Dual Antiplatelet Therapy With 12 Months of Dual Antiplatelet Therapy in Patients With Acute Coronary Syndrome

Abstract: IMPORTANCEClopidogrel monotherapy after short dual antiplatelet therapy (DAPT) after percutaneous coronary intervention (PCI) has not yet been fully investigated in patients with acute coronary syndrome (ACS).OBJECTIVE To test the hypothesis of noninferiority of 1 to 2 months of DAPT compared with 12 months of DAPT for a composite end point of cardiovascular and bleeding events in patients with ACS. DESIGN, SETTING, AND PARTICIPANTSThis multicenter, open-label, randomized clinical trial enrolled 4169 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
97
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 195 publications
(104 citation statements)
references
References 34 publications
2
97
0
5
Order By: Relevance
“… b The 2020 ESC guidelines definition of complex coronary includes but is not limited to the following: coronary stenosis which only can be solved with bifurcation stenting with 2 stents, with very long and small stents, with >3 stents, with >3 stented lesions. 165 ACS = acute coronary syndrome; STEM = ST elevation MI. …”
Section: Antiplatelet Therapymentioning
confidence: 99%
See 1 more Smart Citation
“… b The 2020 ESC guidelines definition of complex coronary includes but is not limited to the following: coronary stenosis which only can be solved with bifurcation stenting with 2 stents, with very long and small stents, with >3 stents, with >3 stented lesions. 165 ACS = acute coronary syndrome; STEM = ST elevation MI. …”
Section: Antiplatelet Therapymentioning
confidence: 99%
“…Recent noninferiority studies have shown that de-escalation to SAPT after a DAPT duration of only 3 months with clopidogrel post-PCI for ACS and after 1 month post-PCI for stable chronic coronary syndrome, is safe, particularly in vulnerable patient groups. 140 , 165 167 This strategy may also be adopted in patients with TP, in whom the indication for DAPT should be re-evaluated when TP occurs as well. Thus, in the context of TP, one should consider the relatively lower bleeding risk associated with DAPT with clopidogrel as compared to DAPT with ticagrelor or prasugrel.…”
Section: Antiplatelet Therapymentioning
confidence: 99%
“…In addition, there is an unmet need for revealing the optimal intensity of P2Y 12 inhibitor monotherapy following dropping aspirin. In the STOPDAPT-2 ACS trial (Short and Optimal Duration of Dual Antiplatelet Therapy After Everolimus-Eluting Cobalt-Chromium Stent-2 in Patient With Acute Coronary Syndrome) 10 enrolling Japanese ACS patients (n=4136), short-term DAPT strategy (clopidogrel monotherapy following 1-month DAPT) was associated with the increased risk of myocardial infarction (1.59% versus 0.85%) and a numerical increase of stent thrombosis (0.45% versus 0.20%), albeit at the benefit of a lower incidence of Bleeding Academic Research Consortium 3 or 5 bleeding (0.54% versus 1.31%) compared with the 12-month DAPT strategy. Aspirin discontinuation with clopidogrel monotherapy in the early phase (within 1 month) may increase the risk of ischemic events even in ACS patients with low thrombotic risk (eg, East Asian patients).…”
mentioning
confidence: 99%
“…13 In contrast, a trial testing a similar concept using clopidogrel instead of ticagrelor after an acute coronary event reported a less favourable ischaemic risk in the clopidogrel monotherapy arm. 14 Whether and how to apply the accumulating data using abbreviated or de-escalated antiplatelet therapy after revascularisation or acute coronary events is a complex decision that requires an in-depth understanding of the different study designs, study populations, antiplatelet agents and the specific ischaemic and bleeding risk of the patient, as was recently shown. 15 A trial specifically targeting patients at high risk of bleeding reported that, following percutaneous coronary revascularisation, the discontinuation of aspirin after 1 month reduced the risk of actionable bleeding with a neutral effect on ischaemic events when compared to the continuation of dual antiplatelet therapy for 12 months.…”
mentioning
confidence: 99%
“…A blinded trial of 7119 patients who were randomised after receiving dual antiplatelet therapy for 3 months following revascularisation reported lower bleeding and non‐inferior ischaemic risk reduction in the intervention arm treated with ticagrelor monotherapy when compared to the control group of ticagrelor plus aspirin for the remaining 12 months 13 . In contrast, a trial testing a similar concept using clopidogrel instead of ticagrelor after an acute coronary event reported a less favourable ischaemic risk in the clopidogrel monotherapy arm 14 . Whether and how to apply the accumulating data using abbreviated or de‐escalated antiplatelet therapy after revascularisation or acute coronary events is a complex decision that requires an in‐depth understanding of the different study designs, study populations, antiplatelet agents and the specific ischaemic and bleeding risk of the patient, as was recently shown 15 .…”
mentioning
confidence: 99%